2020
DOI: 10.1002/jlb.5a0420-231rr
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte subsets predict mortality after cardiac arrest

Abstract: After successful cardiopulmonary resuscitation (CPR), many patients show signs of an overactive immune activation. Monocytes are a heterogeneous cell population that can be distinguished into 3 subsets by flow cytometry (classical monocytes [CM: CD14 ++ CD16-], intermediate monocytes [IM: CD14 ++ CD16 + CCR2 + ] and non-classical monocytes [NCM: CD14 + CD16 ++ CCR2-]). Fiftythree patients admitted to the medical intensive care unit (ICU) after cardiac arrest were included. Blood was taken on admission and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
(93 reference statements)
1
17
0
Order By: Relevance
“…Alternatively, both an increased cell death rate following bacterial challenge 24 and glucocorticoid-induced monocytopenia 25 could possibly explain the relative decrease in nonclassical monocytes after cardiac arrest. Recently, Krychtiuk et al demonstrated that an expansion of the subset of intermediate monocytes and a decrease of the subset of classical monocytes during the recovery phase of PCAS (> 72 h following cardiac arrest) were associated with poor outcome 26 . The present study focused on the early and intermediate phases of PCAS and therefore provides additional insights into monocyte subset kinetics by revealing the almost complete decline in nonclassical monocytes during the early phase of PCAS.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, both an increased cell death rate following bacterial challenge 24 and glucocorticoid-induced monocytopenia 25 could possibly explain the relative decrease in nonclassical monocytes after cardiac arrest. Recently, Krychtiuk et al demonstrated that an expansion of the subset of intermediate monocytes and a decrease of the subset of classical monocytes during the recovery phase of PCAS (> 72 h following cardiac arrest) were associated with poor outcome 26 . The present study focused on the early and intermediate phases of PCAS and therefore provides additional insights into monocyte subset kinetics by revealing the almost complete decline in nonclassical monocytes during the early phase of PCAS.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,9,10 A general loss of intermediate and/or nonclassical monocytes has also been observed in patients with acute and severe cases of COVID-19, 6,7,[10][11][12] with an increased proportion of nonclassical monocytes and DCs migrating to the lungs. 10,13 We have recently identified 8 monocyte subsets in healthy humans, 14,15 and we and others have observed that monocyte subsets can have unique contributions to the progression of disease, 14,16 but detailed analyses of monocyte subsets in COVID-19 are still just emerging. 6,[11][12][13]17,18 Herein, we utilized cytometry by time-of-flight (CyTOF) to identify monocyte (Mo) and DC subsets from healthy subjects and COVID-19 patients that could regulate the immune response to SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Human monocytes are a heterogeneous cell population that can be divided into three major subsets: classical monocytes (CD14 ++ CD16 dim ), intermediate monocytes (CD14 ++ CD16 + ) and non-classical monocytes (CD14 dim CD16 ++ ) [23,24]. Functional observations of human monocyte subsets documented in the literature are controversial, with different responses observed depending on the context of their activation and underlying disease.…”
Section: Discussionmentioning
confidence: 99%